PERAN MODERASI INDIKATOR MAKROEKONOMI PADA FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN - Azizah; Siregar, Hermanto; Sasongko, Hendro (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2023)
This study analyzes the determinants of firm value and the moderating role of macroeconomic indicators on the determinants of firm value. Secondary data testing was carried out on the IDX High Dividend 20 company financial statements for the period 2017-2021 which were analyzed using panel data regression. The determinants of firm value tested include dividend policy, capital structure, ownership, free cash flow, profitability, and good corporate governance (GCG). Interest and exchange rates are used as moderating variables. The research findings show that dividend policy, ownership, and board size have a positive impact, while the audit committee has a negative effect on firm value. The moderating role of interest rates and exchange rates can be seen in their interactions with dividend policy variables and GCG variables which are proxied through the board size and audit committee. The moderating role of interest rates can increase the firm value if it interacts with the dividend policy, and interest rates can increase or decrease a firm value if it interacts with good corporate governance. The exchange rate moderating effect can increase the firm value if it interacts with dividend policy and GCG.